Triflimide-catalyzed allyl–allyl cross-coupling : a metal-free allylic alkylation - Ding, Feiqing (2013)
A highly efficient metal-free intermolecular C(sp3)–C(sp3) allyl–allyl cross-coupling protocol between allyl acetates and allyltrimethylsilanes, which proceeded smoothly in the presence of catalytic triflimide to form 1,5-dienes with good to excellent regioselectivity, has been developed.